Pengaruh Harga Dan Kualitas Produk Terhadap Volume Penjualan Menurut Perspektif Ekonomi Syariah - Albadiah, Ilmi (STAI La Tansa Mashiro, 2020)
This research is motivated by increasingly dynamic developments, humans are required to act quickly and precisely so as not to compete with others. Basically, sales volume in a company is closely related to consumer behavior. Consumer behavior is an important element in trading/entrepreneurship activities, therefore companies need to know about consumer behavior, because companies basically do not know what is in a consumer's mind at the time before, during or after purchasing the product, there is a tendency to influence the price and quality of the product on the sales volume made by consumers, suggests that company management needs to consider aspects of consumer behavior, especially the sales volume at the company. This research aims to determine the effect of price and product quality on sales volume and views on Sharia Economics among customers of Gerai Fasih Rangkasbitung products. Data collection in this research was carried out using questionnaires and documentation. The sample used was purposive sampling with a sample of 30 people and analysis of research data using multiple linear regression analysis using the SPSS version 20 program. Based on the test results, it shows that price has a positive and significant effect on sales volume with a value of tcount (3.923) > ttable (1, 70562). Partially, product quality has no effect on sales volume with a value of tcount (0.587) < ttable (1.70562). Simultaneously, price and product quality have a positive effect on sales volume with a value of fcount (18.573) > ftable (3.34). The Adjust R Square value obtained was 0.584 or 5.84%, meaning that the price and product quality variables had an influence on sales volume of 5.84%, while the remaining 41.6% was influenced or explained by other variables not included in this research model.Keywords: Price, Product Quality, Sales Volume